The Behavior of Students in Purchasing Gadgets in a Corona Pandemic Situation in Medan Indonesia - Effendi, Ihsan; Berampu, Lailan Tawila (International Journal of Psychosocial Rehabilitation, 2020)
The rationale of this research is to form university student consumer model in purchasing in gadgets to support their study during pandemic Covid 19. This research conducted is to understand students’ intention to in purchasing gadget; it also explores the intervening effect of intention on students as Consumer. The purpose of this study is to build student purchasing model in pandemic era where students were force to study online. The subject of his study is student of Faculty of Economics and Business (FEB), Medan Area University in Medan North Sumatra. This study consists of 267 respondents that uses gadget for online learning. The results of the study revealed that college students buy gadgets for college needs prioritizing usability rather than price and ease of use of gadgets.